Randomized, Double-Blind Evaluation of Late Boost Strategies for HIV-Uninfected Vaccine Recipients in the RV144 HIV Vaccine Efficacy Trial. (21st February 2017) - Rerks-Ngarm, Supachai; Pitisuttithum, Punnee; Excler, Jean-Louis; Nitayaphan, Sorachai; Kaewkungwal, Jaranit; Premsri, Nakorn; Kunasol, Prayura; Karasavvas, Nicos; Schuetz, Alexandra; Ngauy, Viseth; Sinangil, Faruk; Dawson, Peter; et al.
Abstract: Background: The RV144 ALVAC-HIV prime, AIDSVAX B/E boost afforded 60% efficacy against human immunodeficiency virus (HIV) acquisition at 1 year, waning to 31.2% after 3.5 years. We hypothesized that additional vaccinations might augment immune correlates of protection. Methods: In a randomized placebo-controlled double-blind study of 162 HIV-negative RV144 vaccine recipients, we evaluated 2 additional boosts, given 6–8 years since RV144 vaccination, for safety and immunogenicity, at weeks 0 and 24. Study groups 1–3 received ALVAC-HIV+AIDSVAX B/E, AIDSVAX B/E, and ALVAC-HIV, respectively, or placebo. Results: Vaccines were well tolerated. For groups 1 and 2, plasma immunoglobulin (Ig) G, IgA, and neutralizing antibody responses at week 2 were all significantly higher than 2 weeks after the last RV144 vaccination. IgG titers against glycoprotein (gp) 70V1V2 92TH023 increased 14-fold compared with 2 weeks after the last RV144 vaccination (14069 vs 999; P < .001). Groups 1 and 2 did not differ significantly from each other, whereas group 3 was similar to placebo recipients. Responses in groups 1 and 2 declined by week 24 but were boosted by the second vaccination, albeit at lower magnitude than for week 2. Conclusions: In RV144 vaccinees, AIDSVAX B/E with or without ALVAC-HIV 6–8 years after initial vaccination generated higher humoral responses than after RV144, but these responses were short-lived, and their magnitude did not increase with subsequent boost. Clinical Trials Registration: NCT01435135.